Thermodynamic, structural and surface properties of Cu–Zr liquid alloy at different temperatures: A theoretical approach - Yadav, Shashit Kumar; Yadav, Deepak Rohita; Gohivar, Ramesh Kumar; Mehta, Upendra (BIBECHANA, 2024)
Quasi-lattice model has been employed to study the thermodynamic and microscopic structural properties of Cu–Zr liquid alloy in the temperature range 1400-1700 K. The model fit parameters required for the purpose have been optimised using the available literature data of thermodynamic properties at the melting temperature of the system, 1400 K. These model parameters have been then computed at different temperatures assuming them to be linear temperature-dependent. The surface properties of the system have been computed using But- ler model at above mentioned temperatures.